133k views
8 votes
Expand the expression

pls as soon as possible​

Expand the expression pls as soon as possible​-example-1

1 Answer

8 votes


\bold{\huge{\underline{Solutions }}}

Expression ( a) :-


\bold{\red{ 2(3 + m) }}


\sf{ = 2 }{\sf{*{3 + 2}}}{\sf{*{m}}}


\sf{ = 6 + 2m}

Expression (b)


\bold{\red{ 5(2+ l) }}


\sf{ = 5 }{\sf{*{2 + 5}}}{\sf{*{l}}}


\sf{ = 10 + 5l}

Expression ( c) :-


\bold{\red{ 3(4 - y) }}


\sf{ = 3 }{\sf{*{4 - 3}}}{\sf{*{y}}}


\sf{ = 12 - 3y }

Expression (d) :-


\bold{\red{ 4(5+ 2k ) }}


\sf{ = 4 }{\sf{*{5 + 4 }}}{\sf{*{2k}}}


\sf{ = 20 + 8k }

Expression ( e) :-


\bold{\red{ 3( 2 - 4f) }}


\sf{ = 3 }{\sf{*{2 - 3}}}{\sf{*{4f}}}


\sf{ = 6 - 12f }

Expression ( f) :-


\bold{\red{ 2(5 - 3w) }}


\sf{ = 2 }{\sf{*{5 - 2}}}{\sf{*{3w}}}


\sf{ = 10 - 6w}

Expression (g) :-


\bold{\red{ 5(2k + 3m) }}


\sf{ = 5 }{\sf{*{2k + 5}}}{\sf{*{3m}}}


\sf{ = 10k + 15m}

Expression (h) :-


\bold{\red{ 4(3d - 2n) }}


\sf{ = 4 }{\sf{*{3d - 4}}}{\sf{*{2n}}}


\sf{ = 12d - 8n }

Expression (i) :-


\bold{\red{ t(t + 3) }}


\sf{ = t }{\sf{*{t + t}}}{\sf{*{3}}}


\sf{ = t^(2) + 3t }

Expression (j) :-


\bold{\red{ k(k - 3) }}


\sf{ = k }{\sf{*{k - k}}}{\sf{*{3}}}


\sf{ = k^(2) + 3k}

Expression (k) :-


\bold{\red{ 4t(t - 1) }}


\sf{ = 4t }{\sf{*{t - 4t}}}{\sf{*{1}}}


\sf{ = 4t^(2) - 4t}

Expression (I) :-


\bold{\red{ 2k(4 - k) }}


\sf{ = 2k }{\sf{*{4 - 2k}}}{\sf{*{k}}}


\sf{ = 8k - 2k^(2)}

User Mika Tuupola
by
5.3k points